Removal of Hexavalent Chromium from Water by Chitosan-Enhanced Ultrafiltration - Indiasih, Putu A. Y.; Syaifudin, Anindita D.; Himma, Nurul Faiqotul; Ismuyanto, Bambang (Makara Journal of Technology, 2023)
Polymer-enhanced ultrafiltration has gained increasing attention as a selective separation process to remove small solutes, such as metal ions, from water or wastewater. Hexavalent chromium Cr(VI) is one of the metal ions in wastewater that has received considerable attention because of its toxicity. Chitosan was used in this study as the polymer to bind Cr(VI) to enhance its removal by ultrafiltration. The effects of chitosan-to-Cr(VI) ratio on Cr(VI) rejection and permeate flux were investigated. In addition, the fouling tendency was evaluated. Results showed that the addition of chitosan with a mass ratio of 12.5 increased the Cr (VI) rejection from 28% to 75% with a slight reduction in permeate flux from 12.5 L.m−2.h−1 to 9.3 L.m−2.h−1. Moreover, the reduced flux after 100 min of operation could be recovered using the backwash procedure by 89% compared to the initial flux.